2007
DOI: 10.1177/0192513x07302726
|View full text |Cite
|
Sign up to set email alerts
|

Children's Reported Communication With Their Parents About War

Abstract: There is increased interest by parents in communicating with their children about political violence. However, limited attention in the scholarly literature has focused on parent—child communication about war and terrorism. In response, the purpose of this study is to assess, within their respective ecological contexts, American and Northern Irish children's ( n = 97) reported communication with their parents about war. The results provide support for the presence of developmental differences, with age being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The relatively young age of many of the children meant that the women shared the desire to shield them from what was deemed harmful knowledge and painful feelings. This finding fits those revealed by a study of American and Northern Irish children's (aged 3-6 and 7-11) reported conversations with their parents about war and political violence which found that age was a stronger predictor than gender and country in determining whether or not children discuss war with their parents (O'Malley et al, 2007). Yet, the mothers were well aware (sometimes taken aback, sometimes proud) that even their very young children were not only exposed to, but could also formulate a stand regarding the military conflict.…”
Section: Talksupporting
confidence: 89%
See 1 more Smart Citation
“…The relatively young age of many of the children meant that the women shared the desire to shield them from what was deemed harmful knowledge and painful feelings. This finding fits those revealed by a study of American and Northern Irish children's (aged 3-6 and 7-11) reported conversations with their parents about war and political violence which found that age was a stronger predictor than gender and country in determining whether or not children discuss war with their parents (O'Malley et al, 2007). Yet, the mothers were well aware (sometimes taken aback, sometimes proud) that even their very young children were not only exposed to, but could also formulate a stand regarding the military conflict.…”
Section: Talksupporting
confidence: 89%
“…Yet, to the best of our knowledge, there are surprisingly few studies that address communications between parents and young children about political violence in Israel, or elsewhere (cf. O’Malley et al, 2007).…”
Section: Conceptual Underpinningsmentioning
confidence: 99%
“…Whereas they neither exhibited signs of anxiety and other negative outcomes nor mentioned any family Downloaded by [The University of Manchester Library] at 09:21 22 December 2014 discussions about political conflict (as might be expected, see O'Malley, Blankemeyer, Walker, & Dellmann-Jenkins, 2007), it was striking how often and to what extent Lebanese children discussed their desire to help Lebanese people in their careers. They talked about becoming soldiers to fight "the bad guys" and to protect the Lebanese people but a military career was one of many that would involve protecting, helping, and restoring communities.…”
Section: Articulating Meaningfulness Based On Local Contextsmentioning
confidence: 95%
“…A structured interview procedure with open‐ended questions was selected to collect data. The interview questions used in this study were developed by a research team and have been used for collecting data in other research projects to study children's and parents' perceptions about peace‐ and war‐related concepts and issues (Deng, 2008; Deng & Shih, 2009; Myers‐Bowman et al, 2003, 2005; O’Malley et al, 2007). For this study, parents' and children's responses related to the research questions were used and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The most common theme in parental descriptions of peace to their children was identifying “what peace is not.” The authors reported that many parents in their study did not talk to children about peace and war using developmentally appropriate techniques. Regarding parent‐child communication about peace and war, O’Malley, Blankemeyer, Walker, and Dellmann‐Jenkins (2007) reported that older American boys were more likely than younger ones to report talking to their parents about war. This developmental difference, however, was not found among Northern Irish children in the study.…”
Section: Parents and Children Peace And Warmentioning
confidence: 99%